Flowering Plants : Basswoods to Spurges - Mohlenbrock, Robert H. (Book collections on Project MUSE., 1982)
This is the fourth volume in The Illustrated Flora of Illinois devoted to dicotyledons, or dicot plants. Dicots are the greatest group of flowering plants, exceeding the monocotyledons, or monocots. Dicots produce a pair of seed leaves during germination while monocots produce only a single seed leaf. This volume contains four orders and ten families of dicots. The orders included in this volume are Malvales, Urticales, Rhamnales, and Euphorbiales. Within the Malvales are the families Tiliaceae, Sterculiaceae, and Malvaceae. The families Ulmaceae, Moraceae, and Urt.